2005
DOI: 10.1016/j.otohns.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use of Facial Nerve Monitoring During Parotid Gland Surgery

Abstract: Permanent facial nerve paralysis after parotidectomy occurs in 0-7% of cases. Currently, a majority of otolaryngologists in the United States are employing facial nerve monitoring during parotid surgery some or all of the time, even though no studies to date have demonstrated improved outcomes with its use. Physician training background and surgery caseload were significant factors influencing usage of facial nerve monitoring in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 14 publications
0
56
0
1
Order By: Relevance
“…This is a common limitation of voluntary surveys and for this reason a reminder email was sent during the data collection phase. Despite this, our response rate was less than that of the other survey-based studies examined [15][16][17][18]. As a consequence of this limitation, the results may be confounded by selection bias.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This is a common limitation of voluntary surveys and for this reason a reminder email was sent during the data collection phase. Despite this, our response rate was less than that of the other survey-based studies examined [15][16][17][18]. As a consequence of this limitation, the results may be confounded by selection bias.…”
Section: Discussionmentioning
confidence: 74%
“…In the case of thyroid and mastoid surgery, this is a higher usage rate than that reflected by the UK and USA studies [15,17,18]. In the case of parotid surgery, it is a similar rate to that described in the UK study and higher than that described in the US study [15,16]. It should be noted that the abovementioned studies were published between two and 10 years ago, and our reported rates may reflect the changing attitudes towards intraoperative nerve monitoring and its availability to surgeons.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Intraoperative facial nerve monitoring during parotid surgery allows for early identification of the FN, mapping of its course through the facial region, warning of unexpected stimulation during dissection, and determination of FN prognosis at conclusion of surgery. A majority of otolaryngologists in the U.S. use some form of intraoperative nerve monitoring during parotid gland surgery [10]. Current methods of intraoperaFacial nerve Lymphangioma Monitoring Mapping…”
Section: Introductionmentioning
confidence: 99%